Business cycles association in a small monetary union: The case of Switzerland - Ferreira-Lopes, A.; T. N. Sequeira (Spatial Economic Analysis, 2012)
With its German, French, Italian, and Romansch Cantons, the Helvetic Federation is a small-scale version of the cultural, social, religious, and linguistic heterogeneities found in the European Union (EU). Although it is an interesting case study for observing the effects of idiosyncratic shocks within regional economies, few studies have been conducted that address Switzerland and the lessons it might hold for the EU, especially for the members of the European Monetary Union (EMU). We study the connections between the business cycles of Swiss regions. Evidence shows that Swiss cantons are closely related but there are dynamic effects toward more ‘independent’ business cycles. Despite the economic and cultural heterogeneity, Swiss cantons remain in the same political and monetary union, sharing a common central bank and a coordination/equalization mechanism for managing independent fiscal policies. Switzerland's ability to do these things should be a matter of interest to the EU.